Management Models for Business Incubators - Machado, AdB; Catapan, AH; Sousa, MJ; Andreia de Bem Machado; Machado, A. De Bem; Andreia de Bem Machado; Machado, A. De Bem; Araci Hack Catapan; Sousa, M. (International Journal of Technology Diffusion, 2020)
The primary goal of this research is to do a systematic review about management models for business incubators. Management models are grounded in three basic pillars: people, processes, and technologies. In this scenario, the business incubator management model is fundamental because it is important for business incubators to meet the demands of new entrepreneurs and entrepreneurship. Therefore, the objective of thisresearch isto map the light of the systematic review of business incubator management models on the world stage. To do so, the methodology used was the integrative review of the literature using the Scopus database and regulations, international and national documents. As a result, one of the problems found in these models was that most business incubator management models describe a business incubator as a transformation mechanism, but do notspell out details about the incubation process or models and best practicesfor businessincubators. management for the continuous improvement of incubated enterprises.